The development of the Ukrainian Shield was 2.7-2.3 billion years ago. Facts and preliminary conclusions - Usenko, O.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The article includes the facts (isotope age of zircons of magmatic and metamorphic rocks, as well as features of the material composition and structure) indicating the course of the geodynamic process on the Ukrainian Shield in the period 2.7-2.3 billion years ago.